The Length and Flexibility of the 2‐Substituent of 9‐Ethyladenine Derivatives Modulate Affinity and Selectivity for the Human A2A Adenosine Receptor. (1st April 2016) - Thomas, Ajiroghene; Buccioni, Michela; Dal Ben, Diego; Lambertucci, Catia; Marucci, Gabriella; Santinelli, Claudia; Spinaci, Andrea; Kachler, Sonja; Klotz, Karl‐Norbert; Volpini, Rosaria
Abstract: The A2A adenosine receptor (A2A AR) is a key target for the development of pharmacological tools for the treatment of central nervous system disorders. Previous works have demonstrated that the insertion of substituents at various positions on adenine leads to A2A AR antagonists with affinity in the micromolar to nanomolar range. In this work, a series of 9‐ethyladenine derivatives bearing phenylalkylamino, phenylakyloxy or phenylakylthio groups of different lengths at the 2‐position were synthesised and tested against the human adenosine receptors. The derivatives showed sub‐micromolar affinity for these membrane proteins. The further introduction of a bromine atom at the 8‐position has the effect of improving the affinity and selectivity for all ARs and led to compounds that are able bind to the A2A AR subtype at low nanomolar levels. Functional studies confirmed that the new adenine derivatives behave as A2A AR antagonists with half‐maximal inhibitory concentration values in the nanomolar range. Molecular modelling studies provide a description of the possible binding mode of these compounds at the A2A AR and an interpretation of the affinity data at this AR subtype. Abstract : Size matters : Substituted 9‐ethyladenine derivatives were synthesised and tested for affinity to the human A2A adenosine receptor. The new adenine derivatives behave as A2A adenosine receptor antagonists with half‐maximal inhibitory concentration values in the nanomolar range. Molecular modelling studies provide a description of the possible binding mode of the compounds and an interpretation of the affinity data.